Potensi Larvasidal Ekstrak Bunga Telang (Clitoria Ternatea) terhadap Kematian Larva Aedes Aegypti - Zahara Fadilla; Aulia Mutiara Hikmah; Azis Rizqi Habibie (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus (DENV), which is transmitted through the bite of Aedes aegypti mosquitoes. These mosquitoes act as the primary vectors carrying the dengue virus. The spread of DHF primarily occurs in tropical and subtropical regions. Mosquito control can be carried out using various methods, one of which is chemical control. However, the long-term use of chemical insecticides may lead to mosquito resistance, highlighting the need for safer alternatives to synthetic insecticides. One such alternative is the use of plant-based extracts. The butterfly pea plant (Clitoria ternatea) has shown potential as a natural larvicide due to its content of flavonoids, tannins, and anthocyanins, which function as antioxidants and are toxic to mosquito larvae. This study aims to determine the potential of Clitoria ternatea flower extract as a natural larvicide against Aedes aegypti larvae. The results of the effectiveness test showed that Clitoria ternatea flower extract has significant larvicidal potential against Aedes aegypti larvae. Observed larval mortality at 24 hours was 22 larvae at 10% concentration, 23 larvae at 50%, and 25 larvae (100%) at 100% concentration. The LC₅₀ value obtained from the test was 36.78%, indicating the extract's potency as a natural larvicide.